Repetition and Aesthetic Judgment in Post-tonal Music for Large Ensemble and Orchestra - Touizrar, Moe; Knoll, Anna Lena; Siedenburg, Kai (Frontiers in Psychology, 2021)
Post-tonal music often poses perceptual and cognitive challenges for listeners, potentially related to the use of relatively uncommon and unfamiliar musical material and compositional processes. As a basic compositional device, repetition affects memory for music and is structured by composers in very different ways across tonal and post-tonal musical repertoires. Of particular concern is whether post-tonal music exhibits mnemonic affordances that allow listeners to experience a sense of global coherence, and whether repetition correlates strongly with aesthetic judgment. Although previous research suggests that repetition impacts aesthetic preference, empirical research has not mapped out the relationship between repetition and aesthetic judgments across a broad set of post-tonal music. Presenting 14 excerpts, grouped into three categories: tonal, modernist, and post-1970, we observed that indications of repetitions in the music for a group of 60 listeners, with and without musical training, showed significant periods of interindividual synchronization. Aesthetic judgments were assessed by means of ratings for the following parameters: familiarity with the piece, confidence of repetition responses, judgments of affordances for easy listening, coherence, similarity of moments, and recognition, as well as listeners’ liking and interest. A principal component analysis on the joint question data and the repetition responses suggested that two factors account for 92% of variance in the data. These factors were interpreted as dominated by aesthetic judgment and repetition strength. Linear mixed-effects regression indicated that repetition strength generally differed across excerpt category, with modernist excerpts featuring lower repetition strength compared to both post-1970 and tonal excerpts. Aesthetic preference, on the other hand, was lower for excerpts in both the modernist and post-1970 categories when compared to tonal excerpts. The analysis did not reveal difference in response behavior for repetition responses as a function of musical training, though it indicated higher preference of modernist excerpts with increasing levels of musical training. Overall, the results suggest that the two factors, aesthetic judgment and repetition strength, act as independent determinants in the experience of post-tonal music.